Pemberdayaan Komunitas Peternak Sapi Perah oleh Dompet Dhuafa di Desa Singolangu, Kabupaten Magetan - Lavia Vega Aldana; Iza Hanifuddin; Amin Wahyudi (Journal of Economics, Law, and Humanities, 2024)
Dompet Dhuafa is an Islamic philanthropic institution that aims to alleviate poverty by empowering with philanthropic activities and prophetic entrepreneurs. Singolangu Village is one of the villages empowered to improve its welfare with the Lawu Milk Village program in collaboration with the Magetan Livestock Office. Singolangu Village has many advantages, but the community has not been able to increase its natural resources to the maximum so that many of its residents are still below the poverty line, so with the presence of this empowerment, it can alleviate poverty and the community becomes more prosperous and independent.The purpose of this study is to find out how community empowerment carried out by Dompet Dhuafa in terms of Elliot's theory whether the implementation of this empowerment has an impact on improving the economy of the community. The research methodology in this study is descriptive-qualitative, through the processing of primary and secondary data obtained by observation, interviews, and documentation on a group of dairy farmers in Singolangu Village, Magetan Regency. The results of this study show that 1) From the implementation of empowerment carried out by Dompet Dhuafa for dairy farmers is quite good and 2) it has fulfilled the welfare approach, development approach and empowerment approach 2) The factor that influences the implementation of community empowerment in this dairy cattle group is the community that has not been very deep about Islam; Dompet Dhuafa, in its empowerment, only focuses on its economy and does not explore the elements His Islam. 3) The impact of welfare for the community on this group of dairy cows has a significant impact on the economic sector, where these communities can raise their economic level so that they are empowered and can be more independent. The impact of empowerment has met the success indicators.